Guerra cultural de la derecha radical conservadora en TikTok: estudio comparativo de influencers en Peru, Brasil, Francia e Italia - Kanashiro Nakahodo, Lilian (2024)
This research analyzed and compared the construction of discursive values of Radical Right in the Global North and South. We adopted an exploratory-qualitative approach, comparing content from nano influencers on TikTok in Peru, Brazil, France, and Italy to explore the cultural war and how they represent the “enemy of the people”. The methodology was based on four filtering processes. The first focuses on defining nanoinfluencers as the subject of this study. The second involves obtaining accounts via the Influencity platform. The third entails refining accounts using a codebook derived from the existing literature to determine their relevance to content production from a radical right perspective. The fourth process involves selecting videos from July to December 2023, resulting in a sample of n=154 videos. The results show that in Latin America, religious rhetoric is used to emotionally connect with the audience and resist the “progressive dictatorship,” while in Europe, the discourse seeks to distance itself from the already entrenched progressive dictatorship in the government. In Latin America, the goal is to prevent its arrival, whereas in Europe, it is disassociated from progressivism. This study contributes to the analysis of the singularities and contradictions in the discursive production of Latin American Radical Right, expanding the existing literature. © 2024, National University of San Marcos. Faculty of Letters and Human Sciences. All rights reserved.